A study of nucleate bubble growth on microstructured surface through high speed and infrared visualization. (October 2017) - Kim, Seol Ha; Lee, Gi Cheol; Kang, Jun Young; Park, Hyun Sun; Kim, Moo Hwan
Abstract: We studied bubble growth on a microstructured surface during nucleate boiling using optical high-speed and infrared (IR) cameras. The effects of structured surfaces on bubble growth and dynamics were examined and their role analyzed with the use of simple models. A smooth, bare surface was prepared, and four microstructured test sample surfaces were fabricated with microscale gaps ranging from 5 to 80 µm. The optical high-speed camera was used to observe the bubble growth profile with high temporal resolution; the IR camera was focused on the underside of the sample for direct visualization of the boiling process. Overall, the microstructured surfaces produced more bubbles, a lower frequency and nucleation site density than the bare surface for the low heat flux range (100–300 kW/m 2 ), corresponding to the isolated bubble growth regime. The liberated bubble size was dependent on the size of the microstructure gap. Analysis of the high-speed images revealed that the liquid between the microstructures did not evaporate during bubble growth; however, during the initial growth stage, there was a brief period in which the liquid at the nucleation site evaporated. The large surface area and relatively high number of nucleation points contributed to enhanced bubble growth on the structured surfaces.